The effect of salinity on the growth , soluble sugar and mineral ions content of barley plant (Hordeum vulgare L.) and soil properties . - Nahi, Sabah (University of Thi-Qar Journal of Science, 2010)
An experiment in plastic pots was carried out to know the effect of different salt concentration levels (50 , 100 , 150 and 200) mMol /L of NaCl in addition to distill water as a control treatment on the growth , soluble sugar and mineral ions content of barley plant (cv local) and the arable soil properties . The results of the study shows an increase on salinity causing a decrease on the growth of plant in terms of stems length and their dry matter weight , also a decrease observed on the concentrations of reduced sugar (19.75 , 18.625 , 15.19 and 15.875) mg / gm as compared with the concentration (15.185) mg/gm at a control treatment ; while the concentrations of total sugar ( 22.30 , 23.35 , 24.085 and 25.99) mg / gm and sucrose (1.25 , 2.315 , 4.335 and 4.925) mg/gm were increased , as compared with their concentrations (16.525 and 0.65) mg /gm respectively , at a controltreatment . The results showed that , the increase of salinity causes an increase on the concentration of mineral ions (Na , Ca , Mg and Cl) on the shoot part of plant whereas (K) ion was decreased , also the values of pH , EC and the concentrations of mineral ions (Na , Ca , Mg , K and Cl) were increased on the arable soil.